A novel technique for numerical approximation of 1D non-linear coupled Burgers' equation by using cubic Hyperbolic B-spline based Differential quadrature method (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this paper, a novel scheme, cubic Hyperbolic B-spline-based Differential Quadrature Method,is proposed for the solution of 1D non-linear viscous coupled Burgers' equation. The numericalapproximation of this mentioned equation is obtained by using the Hyperbolic B-spline-basedDifferential quadrature method. Hyperbolic B-spline is used as a basis function in DQM in orderto obtain weighting coefficients, then received a set of ODEs is solved by using Strong StabilityPreserving Runge Kutta-43 scheme(SSP-RK43 scheme). The accuracy and effectiveness of thisproposed scheme are tested by using three examples. The obtained results are matched with theprevious results present in the literature of other methods as well as with the exact solutions bymeans of